2007
DOI: 10.1111/j.1445-2197.2007.04175.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Proteins in Clinical Applications

Abstract: The role of bone morphogenetic proteins (BMPs) in bone healing has been shown in numerous animal models. To date, at least 20 BMPs have been identified, some of which have been shown in vitro to stimulate the process of stem cell differentiation into osteoblasts in human and animal models. Having realized the osteoinductive properties of BMPs and having identified their genetic sequences, recombinant gene technology has been used to produce BMPs for clinical application - most commonly, as alternatives or adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
308
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 360 publications
(314 citation statements)
references
References 73 publications
3
308
0
Order By: Relevance
“…Recombinant human BMP-2 protein has been clinically used to enhance bone healing 18,27,28 Although our study did not find a significant difference in TGF-β1 or BMP-2 levels between normal union and nonunion groups which is consistent with previously reported findings, however we found a delayed maximal peak for both TGF-β1 and BMP-2 proteins in nonunion patients as compared to the normal union patients. The peak plasma value of TGF-β1 at 2-week may be explained by the fact that TGF-β1 is released from the granules of platelets during the clotting process soon after trauma 31 .…”
Section: Discussionsupporting
confidence: 92%
“…Recombinant human BMP-2 protein has been clinically used to enhance bone healing 18,27,28 Although our study did not find a significant difference in TGF-β1 or BMP-2 levels between normal union and nonunion groups which is consistent with previously reported findings, however we found a delayed maximal peak for both TGF-β1 and BMP-2 proteins in nonunion patients as compared to the normal union patients. The peak plasma value of TGF-β1 at 2-week may be explained by the fact that TGF-β1 is released from the granules of platelets during the clotting process soon after trauma 31 .…”
Section: Discussionsupporting
confidence: 92%
“…Bmpr1a is a type I receptor that has a high affinity for BMP2 (26) and BMP4 (27), which are expressed in bone. BMPs have been shown to exhibit potent osteogenic activity in vitro (28), and the constitutive activation of BMPs or exogenous application of BMPs can induce ectopic bone formation in vivo (29). Therefore, Bmp4 mRNA showed a rhythmic expression pattern as well as the circadian clock gene Per2 in osteoblasts, which indicated that circadian oscillators regulate Bmp4 expression and may modulate diverse physiological processes in bone metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…BMPs have demonstrated clinical utility for bone regeneration and are available commercially and used therapeutically in open fractures of long bones, nonunions, and spinal fusion. (13) However, this process appears to be rather inefficient because large amounts of BMPs have to be applied to achieve beneficial effects. This might be due at least in part to the fact that BMPs induce expression of the BMP antagonist noggin, (14,15) providing a negative-feedback loop to hamper BMP activity and as a consequence clinical efficacy.…”
mentioning
confidence: 99%